PENERAPAN PROGRAM SEKOLAH RAMAH ANAK SEBAGAI UPAYA PERLINDUNGAN ANAK DARI KEKERASAN DI SDN 060856 KECAMATAN MEDAN PERJUANGAN - SITUMORANG, AMELIA; MUHTAJ, MAJDA EL (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2024)
This research aims to find out how the SRA program has been implemented at SDN 060856 Medan Perjuangan District and the driving factors and obstacles that influence the SRA program at SDN 060856 Medan Perjuangan District. This type of research is descriptive qualitative. This research was carried out using interview and observation methods with informants, namely the head of the SRA team at SDN 060856 Medan Perjuangan District and teachers who had been trained in SRA at SDN 060856 Medan Perjuangan District. Then the data analysis techniques in this research are data presentation, data reduction, and summary creation. SD N 060856 Medan Perjuangan District is committed to creating schools that are child-friendly and free of discrimination through the efforts of the principal and teachers. The school implements strict rules to protect students from violence and harassment, providing strict punishments for perpetrators of violence. The school encourages students to be active learners, the school respects children's opinions and involves them in decision making. Good communication between students and teachers creates an environment that supports children's rights. In addition, the school provides safe, comfortable facilities and a pleasant learning environment in accordance with the Child Friendly School program guidelines. ABSTRAKResearch ini bermaksud guna mengetahui bagaimana penerapan program SRA yang telah dilaksanakan di SDN 060856 Kecamatan Medan Perjuangan serta faktor-faktor pendorong serta kendala yang mempengaruhi program SRA di SDN 060856 Kecamatan Medan Perjuangan. Jenis penelitian ini yaitu deskriptif kualitatif.  Research  ini dilaksanakan dengan metode wawancara serta observasi dengan informan yaitu kepala tim SRA di SDN 060856 Kecamatan Medan Perjuangan serta guru yang telah terlatih SRA di SDN 060856 Kecamatan Medan Perjuangan. Kemudian teknik analisis data di research ini yakni penyajian data, reduksi data, serta pembuatan rangkuman. SD N 060856 Kecamatan Medan Perjuangan berkomitmen menciptakan sekolah yang ramah anak dan bebas diskriminasi melalui upaya kepala sekolah dan guru. Sekolah menerapkan peraturan ketat untuk melindungi siswa dari kekerasan dan pelecehan, memberi hukuman yang tegas bagi pelaku kekerasan. Sekolah mendorong siswa sebagai pembelajar aktif, sekolah menghargai pendapat anak dan melibatkan mereka dalam pengambilan keputusan. Komunikasi yang baik antara siswa dan guru menciptakan lingkungan mendukung hak anak. Selain itu, sekolah menyediakan fasilitas yang aman, nyaman, dan lingkungan belajar yang menyenangkan sesuai dengan pedoman program Sekolah Ramah Anak.